Non-mammalian Hosts and Photobiomodulation: Do All Life-forms Respond to Light? () - Hamblin, Michael R (Photochem Photobiol, 2018)
Photobiomodulation (PBM), also known as low-level laser (light) therapy, was discovered over 50 years ago, but only recently has it been making progress towards wide acceptance. PBM originally used red and near-infrared (NIR) lasers, but now other wavelengths and non-coherent light emitting diodes (LEDs) are being explored. The almost complete lack of side-effects makes the conduction of controlled clinical trials relatively easy. Laboratory research has mainly concentrated on mammalian cells (normal or cancer) in culture, and small rodents (mice and rats) as models of different diseases. A sizeable body of work was carried out in the 1970s and 1980s in Russia looking at various bacterial and fungal cells. The present review will cover some of these studies and a recent number of papers that have applied PBM to so-called “model organisms”. These models include flies (Drosophila), worms (C. elegans), fish (zebrafish), and caterpillars (Galleria). Much knowledge about the genomics and proteomics, and many reagents for these organisms already exist. They are inexpensive to work with and have lower regulatory barriers compared to vertebrate animals. Other researchers have studied different models (snails, sea urchins, Paramecium, toads, frogs and chickens). Plants may respond to NIR light differently from visible light (photosynthesis and photomorphogenesis) but PBM in plants has not been much studied. Veterinarians routinely use PBM to treat non-mammalian patients. The conclusion is that red or NIR light does indeed have significant biological effects conserved over many different kingdoms, and perhaps it is true that “all life-forms respond to light”.